2012
DOI: 10.1002/clen.201200049
|View full text |Cite
|
Sign up to set email alerts
|

Wetland Network Design for Mitigation of Saltwater Intrusion by Transferring Tidal Discharge

Abstract: With the interactions of river discharge and tide, the balances between water and saline in estuaries are helpful for maintaining biodiversity and landscape diversity. However, the delicate balances have been broken in many estuaries especially in some areas where prosperous cities have been developed. Saltwater intrusion causes serious adverse effects on estuary ecosystems in Pearl River estuary (PRE), China. This paper tries to use a wetland network which is a methodology to divert saltwater to explain how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…The basic function of wetlands is to store water. The wetlands involved in a wetland network play an important role in the protection of an estuarine ecosystem 5, which is at the risk of sharp shrink and functional degradation 73, 74. The wetland network method provides a better solution to protection of saltwater intrusion in the PRE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic function of wetlands is to store water. The wetlands involved in a wetland network play an important role in the protection of an estuarine ecosystem 5, which is at the risk of sharp shrink and functional degradation 73, 74. The wetland network method provides a better solution to protection of saltwater intrusion in the PRE.…”
Section: Discussionmentioning
confidence: 99%
“…An estuarine ecosystem, which features the land–ocean interactions of an abundant population of flora and fauna, has the highest service values compared to other ecosystems 1. Meanwhile, it is a sensitive ecosystem to the rapid industrialization and economic development and sea level rise 2–5. With the water shortages and sea level rise, researchers found that the salinity gradient was an important factor in determining these estuarine ecosystem services 6–14.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the wetland network can effectively mitigate the saltwater intrusion by replenishing freshwater stored in the wetland network into river channels in this region. Zhang et al 28 also tried to use a wetland network which is a methodology to divert saltwater to explain how to address the adverse effects of saltwater intrusion and aims to mitigate such intrusion. Yang et al 29 designed a wetland network by linking linear wetlands and patch wetlands, determined the water trade‐off between human use and wetland network and calculated the environmental flow requirement.…”
Section: Previewmentioning
confidence: 99%
“…Furthermore, some N cycling reactions, such as nitrification, are inhibited by high levels of salinity (Joye and Hollibaugh, 1995), while other reactions, such as DNRA, can be enhanced by the same conditions (Giblin et al, 2010(Giblin et al, , 2013. As seawater intrusion from dredging and climate change progresses (Hackney and Yelverton, 1990;Zhang et al, 2012), it is unclear how these changes in water chemistry will effect the microbial communities involved in the N cycle or the interactions among N cycling processes (Santoro, 2010). Therefore, understanding how these projected environmental changes will alter the estuarine N cycle from a whole-ecosystem perspective is a crucial goal for managers and policy makers.…”
Section: Introductionmentioning
confidence: 99%